The Impact of Elementary School Number Learning Module Based on Team-Based Project on Critical Thinking Ability - Mufidah, Mufidah; Akina, Akina; Sani, Nurul Kami; Khairunnisa, Khairunnisa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Critical thinking is needed to seek new ideas and discoveries to solve complex life problems in the 21st century. One effort to meet these needs is to use a supportive learning model based on a team-based project. The model is directed to be able to influence the way of thinking of students who are more critical. However, the implementation of this learning has not been supported by mature learning tools, the modules that are currently owned still have some limitations because they were made at the beginning of the program implementation period and of course during that period certain conditions were found in the field that required adjustments and refinements to fit the context. problems encountered in the field. This research is a Research and Development study that uses the development steps developed by Borg and Gall including: 1) Needs Analysis; 2) Teaching Material Development Planning; 3) Design validation; 4) Product trials in small groups; 5) Product revision; and 6) Product trials on large groups. The data and data sources used are: (1) expert assessment data, (2) trial results data on small groups and (3) test results data on large groups. The implementation of this research was in the Tadulako University PGSD study program and the test subjects were students of the 2019/2010 class. The results of the research that has been carried out are the Team-Based Project-Based SD Numbers Learning Module on the Critical Thinking Ability of PGSD Study Program Students based on the results of validation from material experts and media experts as well as from the results of initial field trials and the results of the main field trials it can be concluded that the numbers learning module SD based Team Based Project for PGSD students is said to be Valid and practical so that this module is feasible to use.